Pengaruh Pembelajaran Media Audio Visual Dalam Menstimulus Moral Anak Usia 5-6 Tahun di PAUD Al-Arif Teko - Moh. Alwi Ashari; Zuhud Ramdani; Nur Adiyah Yuliastri; Dinda Indina (Alpatih Harapan Semesta, 2026)
This study aims to determine the effect of audio-visual media in stimulating the moral development of children aged 5–6 years at PAUD Al-Arif in the 2023/2024 academic year. This research employed a quantitative approach using an experimental method with a pre-experimental one-group pretest–posttest design. The subjects of the study were all 10 children in Group B at PAUD Al-Arif Teko. Data collection instruments included validation sheets, observation sheets, and documentation. The data analysis techniques involved observational analysis, prerequisite tests, and hypothesis testing. The results showed an improvement in children’s moral development, with a pre-test score of 85 and an average percentage of 43% (categorised as “Beginning to Develop”), while the post-test score increased to 181 with an average of 91% (categorised as “Very Well Developed”). The t-test results indicated that t_calculated (16.648) was greater than t_table (1.833), demonstrating a significant effect. Therefore, audio-visual media is effective in enhancing the moral development of children aged 5–6 years at PAUD Al-Arif Teko.